2013
DOI: 10.1055/s-0032-1326348
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of flat lesions in a large screening population and their role in colonoscopy quality improvement

Abstract: Malignant potential of polyps is mostly affected by size but not by shape. Since flat polyp detection rate only correlates poorly with ADR we do not recommend its incorporation in quality assured screening colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
6
23
1
Order By: Relevance
“…A greater malignant potential for lesions >10 mm (P<0.0001) was observed by Reinhart et al (23) , regardless of morphology. However, there have been series showing that small, non-polypoid lesions are more likely to contain carcinoma and a deeper infiltration of the submucosa, when compared to larger, polypoid lesions (14,20,29) .…”
Section: Discussionmentioning
confidence: 55%
“…A greater malignant potential for lesions >10 mm (P<0.0001) was observed by Reinhart et al (23) , regardless of morphology. However, there have been series showing that small, non-polypoid lesions are more likely to contain carcinoma and a deeper infiltration of the submucosa, when compared to larger, polypoid lesions (14,20,29) .…”
Section: Discussionmentioning
confidence: 55%
“…Details about this project were reported elsewhere (Ferlitsch et al , 2011; Bannert et al , 2012; Reinhart et al , 2013; Kozbial et al , 2014; Waldmann et al , 2015). All colonoscopy data of this study performed between November 2008 and December 2012 were assessed within this project, and comprised 80 931 colonoscopies performed in 80 398 persons.…”
Section: Methodsmentioning
confidence: 99%
“…In women and men older than 80 years, the rates increased to 27% and 40%, respectively [1]. A recent population-based study found that at least one polyp was detected in 34.3% of asymptomatic patients undergoing a screening colonoscopy [2]. In autopsy series, the prevalence is even higher and increases with age.…”
Section: Neoplastic Colorectal Polypsmentioning
confidence: 99%